(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A field trial was conducted in one of the fields of Ibn Al-Bitar Preparatory Vocational- Holy Kerbala Governorate, during spring season at 2021, to know the effect of organic fertilizes 0, 2000 Kg ha-1 Cow, 2000 Kg ha-1 Poultry ,1500 Kg ha-1 cow+ 500 Kg ha-1 Poultry,1000 Kg ha-1 cow+1000 Kg ha-1 Poultry and 1750 Kg ha-1 cow+ 250 Kg ha-1 Poultry and spraying with potassium nanoparticals 0,1000 and 2000mg L-1 on some growth characteristics of maize plant. A Randomized Complete Block Design RCBD was used with three replications The data were statistically analyzed using the Genstat program, and the averages were compared with the least significant difference at level 5% . the results showed the 1750 Kg ha-1 cow+ 250 Kg ha-1 Poultry treatment was superior by give highest values in all characteristics under study. Also 2000 mg L-1 treatment from potassium nanoparticals was outperformed in all studied traits Except for the characteristics of ear diameter and stem diameter, they did not differ significantly from treatment K1.